The Relationship Between Chemotherapy And Incidence Of Anemia In Breast Cancer Patients At Cut Meutia General Hospital, North Aceh - Aya Sofia; Adi Rizka; Iskandar Albin (Faculty of Medicine University of Malikussaleh, 2022)
Introduction: Chemotherapy is the most common treatment before and after surgery to treat breast cancer patients, anaemia is the most common side effect of chemotherapy, and transfusion is the most common side effect of chemotherapy treatment. The increase in the haemoglobin levels can be achieved quickly, but the side effects that may occur are also not small. This study aims to determine the relationship between chemotherapy and the incidence of anaemia in breast cancer patients at the Cut Meutia General Hospital, North Aceh Methods: The type of research is analytical, and the method uses a cross-sectional design carried out from October 2021 to March 2022. A total sample of 45 breast cancer patients was taken by total sampling that met the inclusion and exclusion criteria. Results: The results showed that there were 15 people (16.00) of chemotherapy drugs using the platinum base and antrasiklin for 30 people (26.50). Man Whitney test results obtained p <0.007 indicates that the value (p) <0.05 (p = 0.000). Conclusion: So this study concludes that there is a relationship between chemotherapy and the incidence of anaemia in breast cancer patients at RSCM Aceh Utara.